American caudillo: Princely performative populism and democracy in the Americas. (May 2019) - von Vacano, Diego
Populism is on the rise throughout the world and it poses a challenge to democratic theory. Conventional political thought has not dealt seriously with this challenge throughout most of its history. The article takes the challenge seriously, underscoring the rise of Donald Trump as an example of populism. I argue that dominant paradigms in the study of the history of political thought and in normative, Rawlsian approaches do not elucidate populism. I argue that we need to look beyond the mainstream and to comparative political thought in particular. The Latin American political theory tradition, which has been in conversation with European ideas since the dawn of the modern age, provides a model of 'princely performative populism' that is more useful. Drawing on a Machiavellian conception of the prince's aesthetic relationship to the people and the centrality of populist experiences in Latin America (e.g. Juan Domingo Perón, Getúlio Vargas, and Lázaro Cárdenas), my model provides a novel definition of populism emphasizing the leitmotifs of racialism, gender/machismo, caudillismo and the 'civilized versus barbarian' trope.